Significance of interferon signaling based on mRNA-microRNA integration and plasma protein analyses in critically ill COVID-19 patients - Yuki Togami; Hisatake Matsumoto; Jumpei Yoshimura; Tsunehiro Matsubara; Takeshi Ebihara; Hiroshi Matsuura; Yumi Mitsuyama; Takashi Kojima; Masakazu Ishikawa; Fuminori Sugihara; Haruhiko Hirata; Daisuke Okuzaki; et al. (Elsevier, 2022)
We evaluated mRNA and miRNA in COVID-19 patients and elucidated the pathogenesis of COVID-19, including protein profiles, following mRNA and miRNA integration analysis. mRNA and miRNA sequencing was done on admission with whole blood of 5 and 16 healthy controls (HCs) and 10 and 31 critically ill COVID-19 patients (derivation and validation cohorts, respectively). Interferon (IFN)-α2, IFN-β, IFN-γ, interleukin-27, and IFN-λ1 were measured in COVID-19 patients on admission (day 1, 181 critical/22 non-critical patients) and days 6-8 (168 critical patients) and in 19 HCs. In the derivation cohort, 3,488 mRNA and 31 miRNA expressions were identified among differentially expressed RNA expressions in the patients versus those in HCs, and 2,945 mRNA and 32 miRNA expressions in the validation cohort. Canonical pathway analysis showed the IFN signaling pathway to be most activated. The IFN-β plasma level was elevated in line with increased severity compared with HCs, as were IFN-β downstream proteins, such as interleukin-27. IFN-λ1 was higher in non-critically ill patients versus HCs but lower in critical than non-critical patients. Integration of mRNA and miRNA analysis showed activated IFN signaling. Plasma IFN protein profile revealed that IFN-β (type I) and IFN-λ1 (type III) played important roles in COVID-19 disease progression.